Improving surface properties of cathode and increasing abundance of autotrophic bacteria for chromium reduction with amino functionalized carbon nanotubes. Issue 3 (June 2022) - Yu, Xiaodi; Guo, Tiantian; Liu, Xiaoliang; Zhou, Bin; Zhai, Xinru; Yang, Jing; Wang, Xiaohan; Hou, Yunhua; Yang, Qinzheng
Abstract: Chromium reduction by electrochemically active bacteria on the biocathode of bioelectrochemical systems is a promising bioremediation technology. However, the poor conductivity and surface properties of conventional carbon cathode materials greatly limit the adhesion and enrichment of Cr-reducing bacteria on the electrode surface. In our study, a conductive cathode with aminated surface was assembled layer-by-layer with polystyrene sulfonic acid and amino carbon nanotubes (NH2 -CNT). The electrode displayed high chromate ions adsorption capacity, and the sediment microbial fuel cell (SMFC) with it as the cathode output the highest voltage of 241 mV and was able to remove 98 % of the Cr (VI) in the upper water. The attached NH2 -CNT layer promoted the formation of biofilm on the cathode, as well as the secretion of extracellular protein. In addition, the relative abundances of Cr-reducing bacteria, such as Rhodobacter, Hyphomicrobium, Leucobacter, Sphaerotilus and Acetobacterium, were greatly enriched. This significantly increased the chromium reducing rate of the SMFC with NH2 -CNT electrode by 2.06 times, compared with the control. These results suggested that the NH2 -CNT modified cathode could improve the interfacial properties of SMFCs and promote the enrichment of Cr-reducing bacteria. This work provides a new strategy to increase the bioremediation efficiency of heavy metals. Graphical Abstract: ga1 Highlights: A conductive positive charged cathode is prepared by assembling amino carbon nanotube. Modified cathode with aminated surface displays a high chromate and bacteria adsorption. The enrichment of Cr-reducing bacteria enhances the chromium reduction of SMFC.